Taxonomy of Triportheus (Ostariophysi: Triportheidae) from the Paraná-Paraguai basin, South America - Douglas Alves Lopes; Fernando Rogério Carvalho (Neotropical Ichthyology, 2024)
Abstract A taxonomic review of Triportheus from the Paraná-Paraguai basin was conducted, with four valid species recognized: two natives, one introduced in the upper rio Paraná basin, and one new species described herein. Redescriptions, including osteological characters and detailed coloration patterns, are presented for all recognized species. An update on the distribution of Triportheus species in the Paraná-Paraguai basin is provided, along with discussions regarding introductions in the upper rio Paraná basin and hypothesis of occurrences. In this context, a key for the identification of Triportheus species from the rios Paraná-Paraguai basin is also provided.